Peculiarities of the interneuronal pool influence on the spinal motoneurons under the conditions of prolonged hypoestrogenemia - S. S. Tkachenko; O. H. Rodynskyi; H. О. Rodynska; I. V. Horb-Havrylchenko (Zaporožskij Medicinskij Žurnal)
The purpose of research is to study the peculiarities of the interneuronal networks influence on the activity of spinal anterior horns motoneurons under the conditions of experimental menopause.